THE RELEVANCE OF PROPHET MUHAMMAD’S LEADERSHIP AS A MODERN LEADERSHIP ROLE MODEL - Rafiqi Ihsan; Iskandar Ritonga (Sultan Syarif Kasim State Islamic University, Riau, 2022)
AbstractThe era of the Prophet Muhammad did not recognize the science of management and leadership, but he applied the science very well and perfectly. This study aims to explain and analyze the leadership of the Prophet as a modern leadership role model. Researchers use qualitative methods with the type of library research. The data used in this study used secondary data derived from books, Scopus-indexed journals (Q1-Q4), Sinta-indexed (S1-S4), and website articles that are relevant to the research topic. The data analysis technique uses content analysis. Researchers analyzed in depth the content of the sources obtained. The results of this study explain that the life of the Prophet Muhammad is inseparable from his function as a pioneer, aligner, empowerment, and role model. The relevance of the Prophet's leadership as a modern leadership role model is related to the leader's method of overcoming problems in modern times based on Islamic leadership principles for the realization of the maslahah of the ummah.